Bio-materials and prototyping applications in medicine - Bártolo, Paulo Jorge 1968-; Bidanda, Bopaya (Springer, 2021)
Rapid prototyping is used to design and develop medical devices and instrumentation. This book details research in rapid prototyping of bio-materials for medical applications. It provides a wide variety of examples of medical applications using rapid prototyping, including tissue engineering, dental applications, and bone replacement. Coverage also discusses the emergence of computer aided design in the development of prosthetic devices